Preparing for the high frontier : the role and training of NASA astronauts in the post- space shuttle era (National Academies Press, 2011)
As the National Aeronautics and Space Administration (NASA) retires the Space Shuttle and shifts involvement in International Space Station (ISS) operations, changes in the role and requirements of NASA's Astronaut Corps will take place. At the request of NASA, the National Research Council (NRC) addressed three main questions about these changes: what should be the role and size of Johnson Space Center's (JSC) Flight Crew Operations Directorate (FCOD); what will be the requirements of astronaut training facilities; and is the Astronaut Corps' fleet of training aircraft a cost-effective means of preparing astronauts for NASA's spaceflight program? This report presents an assessment of several issues driven by these questions. This report does not address explicitly the future of human spaceflight.